Genotoxicity and by-products assessment in degradation and mineralization of Ciprofloxacin by UV/H2O2 process. Issue 6 (December 2018) - Borba, Fernando H.; Schmitz, Andrieli; Pellenz, Leandro; Bueno, Francine; Kasper, Natan; Wenzel, Bruno M.; Baroni, Suzymeire; Dall'Oglio, Isabella Cristina; Módenes, Aparecido N.
Graphical abstract: Highlights: UV-C/H2 O2 process showed an excellent performance in Ciprofloxacin degradation. Intermediary by-products were identified during the Ciprofloxacin oxidation. Genotoxicity tests verified chromosomal aberrations in the bioindicator Allium cepa . Antibacterial tests were performed in the treated Ciprofloxacin solution. Abstract: In this work, the degradation and mineralization of Ciprofloxacin molecules by an UV-C/H2 O2 process has been investigated, aiming to improve its performance based on a response surface methodology. In the context of the UV-C/H2 O2 process, the influence of the initial H2 O2 concentration and solution pH on Ciprofloxacin degradation performance was investigated for long duration UV irradiation times, up to 600 min. The main by-products yielded from the process were monitored by gas chromatography–mass spectrometry, and the genotoxicity of the effluent was assessed using the bioindicator Allium cepa . The best results for Ciprofloxacin removal were obtained when the reactor was operated at an initial H2 O2 concentration of 200 mg L −1 and solution pH of 3.2. Gas chromatography–mass spectrometry analysis allowed to identify the formation of a series of intermediary by-products, such as phenolic antioxidants and phthalates. From the genotoxicity and antibacterial effects tests, an increase in the mitotic index and a decrease in the inhibition halos of the treated Ciprofloxacin samples for 420 and 600 min irradiation times was observed, suggesting a reduction of the toxic and cytotoxic potential of the main by-products yielded. The UV-C/H2 O2 process-based Ciprofloxacin treatment exhibited an excellent performance and is suggested as an interesting alternative for the reduction of the toxic, carcinogenic, and mutagenic effects caused by the inappropriate disposal of emerging contaminants in water bodies.